The association between vitamin D deficiency and the risk of resistant hypertension. (17th February 2020) - Alagacone, Shiran; Verga, Emanuele; Verdolini, Roberto; Saifullah, Shaik Mohammed
ABSTRACT: Background : Previous studies have already shown a link between vitamin D deficiency and hypertension. The impact of vitamin D deficiency in resistant hypertension is currently unknown. This study examined whether an association between the two entities exists. Method : We analysed 2953 known hypertensive subjects surveyed by NHANES (National Health and Nutrition Examination Survey) among the United States population between 2003 and 2006. Subjects were categorized as having either resistant hypertension or hypertension based on the number of anti-hypertensives in use and their overall blood pressure control. Subjects were also categorized as vitamin D deficient if they had 25(OH)D (25-hydroxycholecalciferol) levels less than 20ng/ml. Results : Out of the 2953 subjects, 362 (12%) were found to have resistant hypertension and 2591 (88%) had controlled hypertension. The prevalence of vitamin D deficiency in resistant hypertension and controlled hypertension groups was 61% and 46% respectively. Following adjustments for other variables such as age, renal function, obesity and ethnicity, the odds ratio (OR) for concomitant presence of resistant hypertension and vitamin D deficiency was 3.49 (95% confidence interval [CI] 1.69–7.17; P < 0.009). The OR for having resistant hypertension and chronic kidney disease, older age and obesity were 2.5 (95% CI 1.5–4; P < 0.0003), 1.034 (95% CI 1.02–1.07; P < 0.0001) and 1.048 (95% CI 1.02–1.07; P < 0.0001) respectively. Conclusion : This study found a statistically significant association between vitamin D deficiency and resistant hypertension. Abbreviations: US, United States; NHANES, National Health and Nutrition Examination Survey; UVB, ultraviolet B; PTH, parathyroid hormone; IRB, Institutional Review Board; NCHS, National Centers for Health Statistics; BMI, body mass index; BP, blood pressure; ACE, angiotensin-converting-enzyme; RIA, Radio Immuno Assay; SAS, Statistical Analysis System; 25(OH)D or 25OHD3, 25-hydroxycholecalciferol or 25-hydroxyvitamin D3 or calcifediol or calcidiol; Vitamin D3, cholecalciferol; OR, odds ratio; CI, confidence interval.